Doxorubicin delivery by polymer nanocarrier based on N-methylglucamine resorcinarene. Issue 2 (1st February 2020) - Sergeeva, Tatiana Yu.; Mukhitova, Rezeda K.; Bakhtiozina, Leysan R.; Nizameev, Irek R.; Kadirov, Marsil K.; Sapunova, Anastasia S.; Voloshina, Alexandra D.; Ziganshina, Albina Y.; Antipin, Igor S.
ABSTRACT: Herein we describe a simple method for the synthesis of polymer nanocarrier for the doxorubicin delivery. The nanocarrier consists of N-methyl-glucamine resorcinarenes that are covalently bound to phenylboronic acid. The nanocarrier is stable at normal pH but is hydrolysed at pH below 6. It demonstrates low cytotoxicity and haemolytic activity. Doxorubicin was successfully loaded into the nanocarriers cavity and its release occurs at pH. Flow cytometry data showed that the carrier improves the penetration of doxorubicin into M-Hela cancer cell lines. The encapsulated doxorubicin demonstrates higher cytotoxicity towards the cancer cells. Abstract : Graphical Abstract